2019
DOI: 10.1111/aas.13413
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms and prediction of chronic post‐surgical pain after hysterectomy—a subgroup analysis of a multicenter cohort study

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.Background: Chronic post-surgical pain (CPSP) is a serious problem. Clinical and psychological variables have not been able to explain all observed variance in prevalence and severity of CPSP. The first objective is to determine the association between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…29 A large body of adult perioperative literature points to the role of the catechol-O-methyltransferase (COMT) gene in modulating pain sensitivity and the incidence of chronic pain. [30][31][32][33][34] One pediatric study found significant relationships between three COMT SNPs and acute postsurgical pain intensity, 35 suggesting a potential role in interindividual variation in postoperative pain perception. Two studies investigated the association between DNA methylation in…”
Section: Genetic Factorsmentioning
confidence: 99%
“…29 A large body of adult perioperative literature points to the role of the catechol-O-methyltransferase (COMT) gene in modulating pain sensitivity and the incidence of chronic pain. [30][31][32][33][34] One pediatric study found significant relationships between three COMT SNPs and acute postsurgical pain intensity, 35 suggesting a potential role in interindividual variation in postoperative pain perception. Two studies investigated the association between DNA methylation in…”
Section: Genetic Factorsmentioning
confidence: 99%
“…It has been shown that the addition of a single polymorphism (SNP rs4818 in COMT) to a prediction model of CPSP enhanced, although not significantly, the prediction power from 78% to 82%. 150…”
Section: Discussionmentioning
confidence: 99%
“…In diabetes and prostate cancer, the predictive accuracy is higher than the currently available clinical models [70]. A recent clinical prediction model on CPSP increased the predictive power of by including a single SNP into the prediction model [7]. This increase in predictive power was not significant but including a complete PRS into the prediction model would significantly improve the clinical prediction modelling [52,62,69,71].…”
Section: Pathway Analysismentioning
confidence: 98%
“…age, biological sex) and psychological (e.g. anxiety) risk factors of CPSP can account for 78% of the variance in the development of CPSP [7,8]. Although recent evidence (both GWAS and gene-Electronic supplementary material The online version of this article (https://doi.org/10.1007/s10048-020-00614-5) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%